Single-stage versus two-stage resection for large anterior midline skull base meningiomas with bihemispheric peritumoral edema - Lina-Elisabeth Qasem; Ali Al-Hilou; Jan Oros; Katharina J. Weber; Fee Keil; Daniel Jussen; Vincent Prinz; Volker Seifert; Peter Baumgarten; Gerhard Marquardt; Marcus Czabanka (Scientific Reports)
Abstract Resection of large anterior midline skull base meningiomas with extensive peritumoral edema poses high risks due to postoperative edema decompensation leading to increased intracranial pressure. Initial craniectomy prevents intracranial pressure decompensation but requires secondary cranioplasty. This study compares single-stage osteoplastic craniotomy with tumor resection to a two-stage approach using bifrontal craniectomy, tumor resection and subsequent cranioplasty after edema recovery in a second surgical step. Patients with large anterior midline skull base meningiomas (> 50 mm) and extensive peritumoral edema were included. Group 1 underwent single-stage resection (2002–2016), while Group 2 had a two-stage approach (2012–2022). The primary outcome was the Karnofsky Performance Scale (KPS) at three months post-surgery. Secondary outcomes included preoperative KPS, KPS at discharge and last follow-up, ICU stay, hospital stay length and complication rates. A total of 25 patients were analyzed (Group 1: n = 9; Group 2: n = 16). Group 2 demonstrated significantly improved KPS at three months postoperatively (median KPS 70% vs. 50%; p = 0.0204) with a non-significant reduction in ICU stay (10 vs. 6.5 days; p = 0.3284). Although no significant differences were observed in KPS at discharge (Group 1: KPS 30% vs. Group 2: KPS 50%; p = 0.1829) or last follow-up (Group 1: KPS 60% vs. Group 2: KPS 80%; p = 0.1630), Group 2 patients required fewer postoperative interventions for complications unrelated to cranioplasty. Overall complication rates were comparable in both groups (Group 1: 67% vs. Group 2: 56%; p = 0.6274). Two-stage resection of large anterior midline skull base meningiomas with extensive edema provides superior clinical outcomes at three months postoperatively without increasing overall complication rates. These findings support the use of a two-stage surgical strategy for highly selected patients. However, further multicenter studies are warranted to validate these results in larger cohorts.